Immaterial Copying in the Age of Access - Foong, Cheryl (Sweet and Maxwell, 2022)
Access models for dissemination of content are increasingly prevalent, yet Australian copyright law does not adequately distinguish background copying from public access to expression. The scope of the reproduction right must be reformulated, as the communication right (which includes ‘making available’) ought to take centre stage in this age of access. In particular, copying for non-expressive use and for non-disseminative purposes should be considered immaterial and beyond the scope of the reproduction right. This comparative article examines judicial and legislative approaches to the issue in various jurisdictions. It proposes a revised infringement analysis for the reproduction right and uses three paradigm scenarios, from text and data mining to examples drawn from US case law, to illustrate its application.